Libraries and AIDS in Sub-Saharan Africa : Realities of Culture and Curriculum - Albright, Kendra; Kigongo-Bukenya, I. M. N. (Proceedings of the American Society for Information Science and Technology, 2006)
The United Nations Educational, Scientific, and Cultural Organization (UNESCO) defines a library as “any organized collection of printed books and periodicals or of any other graphic or audio‐visual materials, and the services of a staff to provide and facilitate the use of such materials as are required to meet the informational, research, educational or recreational needs of its users” (1970). Libraries, by UNESCO definition, are few in SSA, although there are many relevant information related activities. Historically, library and information professionals (LIS) in SSA suffer from the perception that libraries are not necessary. They face obstacles including illiteracy, oral tradition, and a limited awareness of the need for libraries. Despite the perception that libraries are unnecessary in SSA, there are record numbers of professionals graduating from LIS programs and engaged in productive information‐related work. A particular example is the need for information in the fight against AIDS. Information must be organized, managed, and disseminated to help combat the spread of the disease, offering a particular challenge for libraries. This paper presents the preliminary findings of a literature review and survey of library and information professionals in Sub‐Saharan Africa who are involved with HIV/AIDS information dissemination. AIDS information activities are reported, identifying challenges for LIS professionals in Sub‐Saharan Africa and the opportunity for libraries is presented. Implications for LIS education are discussed. Through examination of current information activities related to AIDS, libraries can take an important and more active role while facilitating the identity and reputation of the profession. LIS curriculum could be adjusted to address the unique information needs of Sub‐Saharan societies.